Tyler Perry's Madea goes to jail [videorecording (DVD)] - Perry, Tyler; Luke, Derek, 1974-; Pulliam, Keshia Knight; Overman, Ion, 1976-; Lee, RonReaco; Vergara, Sofía, 1972- (Lionsgate, 2009)
After a high-speed freeway chase puts Madea in front of the judge, her reprieve is short-lived as anger management issues get the best of her and lands her in jail. A gleeful Joe couldn't be happier at Madea's misfortune. But her eccentric family members, the Browns, rally behind her, lending their special 'country' brand of support. Meanwhile, Assistant District Attorney Joshua Hardaway is on the fast track to career success. But Hardaway lands a case too personal to handle - defending Candace Washington, a woman he went to college with and who is now a prostitute and former drug addict. Handling the case would be a conflict of interest, so he asks his fiancée and fellow ADA Linda Holmes to fill in on his behalf. When Candace ends up in jail, Madea befriends the young woman, protecting her in a 'motherly' way as only Madea can.